2017
DOI: 10.1080/00220388.2017.1308489
|View full text |Cite
|
Sign up to set email alerts
|

Allocating Family Responsibilities for Dependent Older People in Mexico and Peru

Abstract: This paper applies different analytical frameworks to explore processes of family bargaining about providing care for dependent older people in Mexico and Peru. These frameworks include cultural norms, life course effects and material exchange. The paper is based on 19 in-depth qualitative family case studies, which are linked to a wider set of quantitative survey data. Care arrangements and bargaining processes are revealed to be highly gendered, and largely conform to prevailing cultural norms. Rather than n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…One study by, Lloyd-Sherlock (2006) found no apparent gender differences in economic vulnerability among Thai older people, suggesting that if gender is likely to be important in understanding why some older people or households are more economically vulnerable than others, its relationship to economic welfare measures is likely to be a complex relationship requiring a more comprehensive approach to uncover the cultural and bargaining processes in Nigerian households. In their recent paper, Lloyd-Sherlock et al (2018) have attempted to capture these bargaining processes for dependent older people in Mexico and Peru using in-depth family case studies linked to a wider set of quantitative survey data.…”
Section: Ols and Quantile Regression Resultsmentioning
confidence: 99%
“…One study by, Lloyd-Sherlock (2006) found no apparent gender differences in economic vulnerability among Thai older people, suggesting that if gender is likely to be important in understanding why some older people or households are more economically vulnerable than others, its relationship to economic welfare measures is likely to be a complex relationship requiring a more comprehensive approach to uncover the cultural and bargaining processes in Nigerian households. In their recent paper, Lloyd-Sherlock et al (2018) have attempted to capture these bargaining processes for dependent older people in Mexico and Peru using in-depth family case studies linked to a wider set of quantitative survey data.…”
Section: Ols and Quantile Regression Resultsmentioning
confidence: 99%
“…The experiences of high-income countries demonstrate a need to develop coordinated, inter-sectoral responses across different agencies 1,11 . There is growing evidence that caring for older family members is highly stressful, physically, financially and emotionally draining 12,13 . This does not mean, however, that formal service provision should be viewed as a direct substitute for family care.…”
Section: Yearmentioning
confidence: 99%
“…Thus, older adults' income and access to healthcare services is heavily dependent on scarce and unreliable social programs and networks (Aguila et al 2011;Garay Villegas, Montes de Oca Zavala, and Guillén 2014;Salgado-de Snyder and Wong 2007). 4 In the particular context of underdeveloped social security systems, which is not unique to Mexico, identifying and understanding the living arrangement dynamics of older people becomes extremely important for both low-and middle-income countries (Lloyd-Sherlock et al 2018). According to Ullmann, Maldonado Valera, and Nieves Rico (2014), in such dissimilar countries as Uruguay, Bolivia, and Mexico, multigenerational households (those with individuals both under 15 and over 65 years old) exhibit the greatest economic vulnerability.…”
Section: Background: Living Arrangements Of Older Adults In Mexicomentioning
confidence: 99%
“…The role of the family as a social institution responsible for the distribution of goods and services between generations has been widely theorized and discussed for a long time ( Angel, Vega, and López-Ortega 2017 ; Becker 1991 ; Economic Commission for Latin America and the Caribbean (ECLAC) 2019 ; Kuznets 1978 ; Thornton, Chang, and Sun 1984 ). In many LIMCs ( Bernabe-Ortiz et al 2016 ), including Mexico ( Lloyd-Sherlock et al 2018 ), strongly gendered norms prevail regarding respect for older people and the responsibility of the young to care for the old as the need arises, Given these socially constructed and situational contexts, it is primarily older adults’ families that provide care and support.…”
Section: Introductionmentioning
confidence: 99%